At the origins of the Jesuit presence in Sardinia - Roberto Ibba (CUHSO)
The contribution proposes the first results of an ongoing research on the presence of the Jesuits in Sardinia between the 16th and 17th centuries. In particular, the focus is on the case study of Sardara where the Jesuits took possession of a house in the centre of the village donated by Canon Giacomo Spiga of the diocese of Ales. The appropriation of ecclesiastical rents by the Company creates considerable tension with the parish priests of the community, who feel that they are impoverished and penalised. The presence of the Company in the village of Sardara, however, contributed to the creation of a ruling class and cultural improvement.